The catechol-O-methyltransferase gene: its regulation and polymorphisms. - Tunbridge, E (2010)
The catechol-O-methyltransferase (COMT) gene is of significant interest to neuroscience, due to its role in modulating dopamine function. COMT is dynamically regulated; its expression is altered during normal brain development and in response to environmental stimuli. In many cases the underlying molecular basis for these effects is unknown; however, in some cases (e.g., estrogenic regulation in the case of sex differences) regulatory mechanisms have been identified. COMT contains several functional polymorphisms and haplotypes, including the well-studied Val158Met polymorphism. Here I review the regulation of COMT and the functional polymorphisms within its sequence with respect to brain function.